Health Problems of Children in Women Jail (Karachi) - Muhammad Irfanullah Siddiqui; Syed Muhammad Maqsood; Abdul Muqtadir; Abbas Hussain (Journal of Bahria University Medical and Dental College, 2011)
Objective:The purpose of this study was to assess the health status & problems of children in women jail Karachi.